Plazovi: Temeljni vodnik o nevarnostih snežnih plazov - Burkeljca, Jernej (University of Maribor Press, 2021)
Avalanches: The Basics of Snow Avalanche Dangers. Anyone who either recreates or works in winter mountain environments has to be aware of avalanches and other dangers related to snow. Avalanches are not limited to steep, high mountain environments. A large amount of snow can also fall off roofs under which small children are playing care-free. Avalanches can happen anywhere there is enough snow on a steep enough slope, even a few steps away from seamingly safe roads, groomed ski runs and houses. Basic awareness and recognition of avalanche dangers is essential to a large population that permanently or just temporarily find themselves in Alpine and other mountain environments.